A novel phase variant of the cholera pathogen shows stress-adaptive cryptic transcriptomic signatures. (December 2016) - Lambert, Bliss; Dassanayake, Maheshi; Oh, Dong-Ha; Garrett, Shana; Lee, Sang-Yeol; Pettis, Gregg
Abstract Background In a process known as phase variation, the marine bacterium and cholera pathogenVibrio cholerae alternately expresses smooth or rugose colonial phenotypes, the latter being associated with advanced biofilm architecture and greater resistance to ecological stress. To define phase variation at the transcriptomic level in pandemicV. cholerae O1 El Tor strain N16961, we compared the RNA-seq-derived transcriptomes among the smooth parent N16961, its rugose derivative (N16961R) and a smooth form obtained directly from the rugose at high frequencies consistent with phase variation (N16961SD). Results Differentially regulated genes which clustered into co-expression groups were identified for specific cellular functions, including acetate metabolism, gluconeogenesis, and anaerobic respiration, suggesting an important link between these processes and biofilm formation in this species. Principal component analysis separated the transcriptome of N16961SD from the other phase variants. Although N16961SD was defective in biofilm formation, transcription of its biofilm-relatedvps andrbm gene clusters was nevertheless elevated as judged by both RNA-seq and RT-qPCR analyses. This transcriptome signature was shared with N16961R, as were others involving two-component signal transduction, chemotaxis, and c-di-GMP synthesis functions. Conclusions Precise turnarounds in gene expression did not accompany reversible phase transitions (i.e., smooth to rugose to smooth) in the cholera pathogen. Transcriptomic signatures consisting of up-regulated genes involved in biofilm formation, environmental sensing and persistence, chemotaxis, and signal transduction, which were shared by N16961R and N16961SD variants, may implicate a stress adaptation in the pathogen that facilitates transition of the N16961SD smooth form back to rugosity should environmental conditions dictate.